Establishing the Identity from the Skeletal Remains of Alum Bheg, a Martyr from the 1857 Indian Freedom Struggle - Kumar, Ashutosh; Ghosh, Sanjib Kumar; Pareek, Vikas (Journal of Morphological Sciences, 2019)
Introduction The present study was undertaken to analyze the morphological features of a skull supposed to be that of Alum Bheg, a martyr from the 1857 Indian Freedom Struggle (also called the Sepoy Mutiny), using established methods to validate identity with regards to age and height as available in the note found with the skull (∼ 32 years old and 5 feet 7½ inch tall).Materials and Methods Identification of the gender of the skull was performed based on established criteria. Analysis for closure of skull sutures (cranial and facial) and measurement of orbitomedial (OM) and maxillomedial (MM) facial anthropometric lines were undertaken to provide an estimated age against each examined suture, as well as against a group of sutures through established scoring systems. Furthermore, the approximate height of the individual was estimated from the skull length using regression equations from a reference adult Indian male population. All of the measurements were made on the digital images of the skull using a digital image analyzer (Image J software, National Institutes of Health, Bethesda, MD, USA).Results Established criteria confirmed that the skull was of a male individual, and the skull sutures and age related morphological changes in the bones indicate that it belonged to an individual in an age range between 20 and 50 years old, with an average of 30 years old, and an approximate height between 5 feet 8.2 inches to 6 feet 1.3 inches.Conclusion The observed values are in approximation with those mentioned in historical notes, and slight differences may be attributed to gross reporting of the original values or limitations of anthropometric analysis. Further biological tests will be required to validate the identity beyond reasonable doubt.
Keywords: alum bheg; anthropometry; identification; 1857 indian freedom struggle; skull